RELATIONSHIP BETWEEN DIET CHRONIC ENERGY LACK IN PREGNANT WOMEN IN TRIMESTER - Saddiyah Rangkuti (RADJA PUBLIKA, 2022)
Chronic lack of energy can occur in pregnant women in the first trimester. Because in the first trimester, the mother's appetite generally decreases, due to frequent nausea and vomiting (morning sickness). Nutrition of pregnant women is influenced by several factors, one of which is diet. This study aims to determine the relationship between diet and Chronic Energy Deficiency in first trimester pregnant women at Pagurawan Health Center, Batu Bara Regency in 2020. This type of research is a quantitative research with a descriptive correlation design with a cross sectional approach. The type of data used is primary data and secondary data collected using a questionnaire sheet and then processed and analyzed using the chi-square test.The results showed that through statistical tests using the chi-square test, the p-value was 0.018 <0.05. It is also known that the OR value = 0.090, meaning that Pregnant who have a poor diet are 0.09 times more at risk of suffering from CED compared to Pregnant who have a good diet. The conclusion is that there is a relationship between diet and Chronic Energy Deficiency in first trimester pregnant women at the Pagurawan Health Center, Batu Bara Regency in 2020. So it is hoped that pregnant women will maintain a healthy diet and eat nutritious food so that nutrition during pregnancy is fulfilled.